Characteristics of exopolysaccharides produced by isolates from natural bioflocculant of Ruditapes philippinarum conglutination mud - Feng, Lijuan; Qian, Tingting; Yang, Guangfeng; Mu, Jun (Frontiers in Microbiology, 2023)
Three novel types of exopolysaccharides (EPS) EPS-S8, EPS-S5, and EPS-F10 were extracted and purified from bacterial isolates Bacillus sp. GHS8, Pseudoalteromonas sp. GHS5 and Psychrobacter sp. GHF10, which were originated from natural bioflocculant of Ruditapes philippinarum conglutination mud (RPM), respectively. The EPS had similar function groups C-H, N-H, C-O, and C = O. The EPS were composed of different monosaccharides (EPS-F10, Man: GlcN: GlcUA: GalUA = 1:0.66:5.75:0.51; EPS-S5, Man: Gal: GlcN: Rib = 1: 0.50: 2.94: 0.26; EPS-S8, Man: Gal: GlcN = 1:1.54:7.69). The molecular weights (Mw) of EPS were ordered as 51.4 kDa (EPS-S5) > 9.15 kDa (EPS-S8) > 4.41 kDa (EPS-F10). Three types of EPS all showed higher peak flocculation activities than the reported crude EPS from the RPM. Besides, the EPS also exhibited efficient decoloration and antioxidation activities, especially for EPS-S8, which might be due to the low Mw and specific monosaccharide composition.